2020
DOI: 10.3390/antibiotics9110739
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Propolis and Antibiotics on Uropathogenic Escherichia coli

Abstract: Urinary tract infections (UTIs) are the most common bacterial infections around the world. Uropathogenic Escherichia coli (UPEC) is among the main pathogens isolated in UTIs. The rate of UPEC with high resistance towards antibiotics and multidrug-resistant bacteria have increased dramatically and conduct to the difficulty to treat UTIs. Due to the rarefaction of new antibiotics molecules, new alternative strategies must be evaluated. Since many years, propolis has demonstrated an interesting antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Despite the various extraction methods and sources of propolis, a number of microbiological studies have shown the enhanced combinatory effect of propolis extracts with different classes of antibiotics in both gram-positive and gram-negative bacteria . In particular, a confirmed synergy by fractional inhibitory concentration (FIC) values was demonstrated in propolis ethanolic extracts with ceftriaxone, ertapenem, and ofloxacin on Escherichia coli ( Lavigne, Ranfaing, 2020 ), oxacillin, and vancomycin on various bacterial strains, including methicillin-resistant Staphylococcus aureus (MRSA) ( Al-Ani, Issam, Zimmermann, Stefan, 2018 ), macrolides on Streptococcus pyogenes and Haemophilus influenzae ( Speciale, Costanzo, 2006 ), and clarithromycin on Helicobacter pylori ( Nostro, Cellini, 2006 ). Remarkably, these above-mentioned antibiotics can be classified into two types based on their mechanistic actions: 1) antibiotics that interrupt the bacterial cell wall (ceftriaxone, ertapenem, oxacillin, and vancomycin) and 2) antibiotics that inhibit bacterial protein synthesis by binding to the bacterial 50S ribosomal subunit (i.e., clarithromycin and macrolides).…”
Section: Pharmacodynamic Interactionsmentioning
confidence: 95%
“…Despite the various extraction methods and sources of propolis, a number of microbiological studies have shown the enhanced combinatory effect of propolis extracts with different classes of antibiotics in both gram-positive and gram-negative bacteria . In particular, a confirmed synergy by fractional inhibitory concentration (FIC) values was demonstrated in propolis ethanolic extracts with ceftriaxone, ertapenem, and ofloxacin on Escherichia coli ( Lavigne, Ranfaing, 2020 ), oxacillin, and vancomycin on various bacterial strains, including methicillin-resistant Staphylococcus aureus (MRSA) ( Al-Ani, Issam, Zimmermann, Stefan, 2018 ), macrolides on Streptococcus pyogenes and Haemophilus influenzae ( Speciale, Costanzo, 2006 ), and clarithromycin on Helicobacter pylori ( Nostro, Cellini, 2006 ). Remarkably, these above-mentioned antibiotics can be classified into two types based on their mechanistic actions: 1) antibiotics that interrupt the bacterial cell wall (ceftriaxone, ertapenem, oxacillin, and vancomycin) and 2) antibiotics that inhibit bacterial protein synthesis by binding to the bacterial 50S ribosomal subunit (i.e., clarithromycin and macrolides).…”
Section: Pharmacodynamic Interactionsmentioning
confidence: 95%
“…Nowadays, the incurable infections caused by multidrug-resistant bacteria remain among the leading causes of mortality in both developed and developing countries. For this, it is essential to find solutions and to develop new strategies to overcome this phenomenon [39,40]. In this context, pollens could represent an appropriate matrix to search for new, safer, and effective antibacterial molecules that can replace or boost the efficiency of conventional antibacterial drugs.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Bee honey and propolis have been used since antiquity due to their health properties. Numerous studies conducted in recent years in various parts of the world highlighted the health benefits of these natural bee products [ 6 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%